2019
DOI: 10.37151/jsma.v11i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Good Corporate Governance Dan Ukuran Perusahaan Terhadap Pengungkapan Sustainability Report

Abstract: Sustainability Report adalah laporan sukarela untuk menyajikan laporan tanggung jawab perusahaan pada aspek sosial, ekonomi dan lingkungan. Sustainability Report dinilai penting untuk keberhasilan jangka panjang, keberlangsungan hidup dan pertumbuhan organisasi. Penelitian ini bertujuan untuk menguji pengaruh good corporate governance dan ukuran perusahaan terhadap pengungkapan sustainability report. Good corporate governance sebagai variabel independen memiliki tiga dimensi variabel yaitu komite audit, komisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
5
7
0
17
Order By: Relevance
“…Therefore, it allows management to prefer to disclose only the necessary reports. The results of this study are in accordance with Dewi and Pitriasari (2019) and Karlina et al (2019).…”
Section: Resultssupporting
confidence: 89%
“…Therefore, it allows management to prefer to disclose only the necessary reports. The results of this study are in accordance with Dewi and Pitriasari (2019) and Karlina et al (2019).…”
Section: Resultssupporting
confidence: 89%
“…The results of this supports the research that has been done by Dewi and Pitriasari (2019) who found that firm size has a positive influence on the disclosure of sustainability reports. In addition, research was done by Khafid and Mulyaningsih (2017), Tobing et al (2019), Barung et al (2018), and Abdulsalam and Babangida (2020) also found similar results that firm size had a positive influence on the disclosure of sustainability reports.…”
Section: Firm Size and Sustainability Report Disclosuresupporting
confidence: 89%
“…The results of this study indicate that firm size has a significant impact on the sustainability report disclosure. Study has been conducted by Khafid and Mulyaningsih (2017), Barung et al (2018), Dewi and Pitriasari (2019), Tobing et al (2019), and Abdulsalam and Babangida (2020) also found that firm size had a positive influence on the disclosure of sustainability reports. In a research has been researched by Oktaviani and Amanah (2019), Hidayah et al (2019), and Ruhana and Hidayah (2020) found evidence that firm size has a negative impact on the publication of sustainability reports because sustainability reports are voluntary, hence many companies are still not involved in publishing sustainability reports.…”
Section: Introductionmentioning
confidence: 98%
“…Research on sustainability reports has found mixed results (Dewi & Pitriasari, 2019) stated in his research that company size and Good Corporate Governance had no effect on the Sustainability Report. However, this statement differs from the research results (Khafid & Mulyaningsih, 2015) which shows that company size affects the Sustainability Report, as well as research by Aniktia and Khafid (2015) which states that Good Corporate Governance affects the publication of the Sustainability Report.…”
Section: Introductionmentioning
confidence: 93%
“…The theory that is usually used as the basis for research on Sustainability Report is the theory of stakeholders or commonly known as Stakeholders Theory. In research of Dewi and Pitriasari (2019) described that Stakeholders Theory is able to expand organizational responsibility not only to investors or company owners but to all stakeholders. The term stakeholder is often used by various parties and its relationship with various sciences such as business management, communication science and so on.…”
Section: Literature Study Stakeholders Theorymentioning
confidence: 99%